Portrait photograph of an unidentified man (location unknown, probably U. S.) - Thayer, Alexander Wheelock, 1817-1897 (previous owner):::Collector:::::::::::: (2023)
Portrait photograph of an unidentified man (undated, location unknown but probably in the United States) from the personal collection of Alexander Wheelock Thayer.